A vacancy-rich perovskite fluoride K0.79Ni0.25Co0.36Mn0.39F2.83@rGO anode for advanced Na-based dual-ion batteries. Issue 47 (18th May 2021) - Tan, Caini; Ding, Rui; Huang, Yuxi; Yan, Tong; Huang, Yongfa; Yang, Feng; Sun, Xiujuan; Gao, Ping; Liu, Enhui
Abstract : A novel concept of Na-ion DIBs was constructed by the vacancy rich perovskite fluoride KNCMF@rGO anode with conversion–insertion hybrid mechanisms. Abstract : A novel concept of Na-based dual-ion batteries (Na-DIBs) has been designed via a perovskite K0.79 Ni0.25 Co0.36 Mn0.39 F2.83 @reduced graphene oxide (KNCMF@rGO) hetero-nanocrystal anode, showing surface conversion and insertion hybrid mechanisms. The KNCMF@rGO//graphite (KS6) DIBs deliver superior energy/power densities and cycling stability and have a significant impact on developing energy storage devices.